A fast-degrading thiol–acrylate based hydrogel for cranial regeneration. (17th March 2017) - Emmakah, A M; Arman, H E; Bragg, J C; Greene, T; Alvarez, MB; Childress, PJ; Goebel, WS; Kacena, MA; Lin, CC; Chu, TM
Abstract: Successful regeneration of the cranium in patients suffering from cranial bone defects is an integral step to restore craniofacial function. However, restoration of craniofacial structure has been challenging due to its complex geometry, limited donor site availability, and poor graft integration. To address these problems, we investigated the use of a thiol–acrylate hydrogel as a cell carrier to facilitate cranial regeneration. Thiol–acrylate hydrogels were formulated with 5–15 wt% poly(ethylene glycol)-diacrylate (PEGDA) and 1–9 mm dithiothreitol (DTT). The degradation rate, swelling ratio, and shear modulus of the resulting hydrogel were first characterized. Then, pre-osteoblast-like cells (MC3T3-E1) were encapsulated in the hydrogel and cultured for up to 21 d. Our results demonstrate that compared to samples formulated from 15 wt% PEGDA, 5 wt% PEGDA samples showed lower storage modulus at day 10 (0.7 kPa versus 8.3 kPa), 62.7% higher in weight change after soaking for 10 d. While the 5 wt% PEGDA group showed an 85% weight loss between day 10 and 21, the 15 wt% PEGDA group showed a 5% weight gain in the same time period. Cell viability with 15 wt% PEGDA and 5 mm DTT hydrogel decreased by 41.3% compared to 5 wt% PEGDA and 5mM DTT gel at day 7. However, histological analysis of cells after 21 d in culture revealed that they had pericellular mineral deposition indicating that the cells were differentiating into osteoblasts lineage in all experimental groups. This study shows that thiol–acrylate hydrogels can be tailored to achieve different degradation rates, in order to enhance cell viability and differentiation. Thus, the findings of this study provide a fundamental understanding for the application of thiol–acrylate hydrogels in cranial bone regeneration.